Shape of Slender Axisymmetric Ventilated Supercavities. (23rd March 2014) - Nesteruk, Igor
Abstract : The integral-differential equation was obtained to simulate unsteady evolutions of the slender axisymmetric ventilated supercavity with the use of one-dimensional inviscid flow of the incompressible gas in the channel between the cavity surface and the body of revolution. For small ventilation rates, the solution of this equation was expressed as asymptotic series. In the steady case the nonlinear differential equation and its solutions were obtained. It was shown that the ventilation can increase and diminish the supercavity dimensions. Examples of calculations for different hull shapes are presented. At some critical values of the gas injection rate the cavity dimensions can become unbounded. Stability of steady and pulsating gas cavities was investigated in the case of the low gas injection rate.